INTENSITY OF OXIDATIVE STRESS IN THE COMORBID COURSE OF NON-ALCOHOLIC STEATOGEPATITIS AND DIABETIC KIDNEY DISEASE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Khukhlina, O.S.; Kotsyubiychuk, Z.Ya.; Antoniv, A.A.; Mandryk, O.Ye.; Voyevidka, O.S. (World of Medicine and Biology, 2021)
75 patients with non-alcoholic steatohepatitis with comorbid type 2 diabetes mellitus and stage I-IV diabetic kidney disease were examined in the treatment dynamics. It was found that the comorbid course of non-alcoholic steatohepatitis and diabetic kidney disease in patients with type 2 diabetes is accompanied by a significant increase in the intensity of oxidative stress, accompanied by an increase in blood intermediate and final products of lipid peroxidation and oxidative modification of proteins in the range of 1.9-2 times (p